The efficacy of a quantitative cross cultural product design survey instrument - Syed Mohamed, Muhammad Syafiq; Mohd Tamrin, Shamsul Bahri; Rahman, R. (American-Eurasian Network for Scientific Information, 2014)
Background/Objectives: Designers and manufacturers often have difficulty in designing products that would be able to meet the demands and needs for various users from different cultures or nations. In an increasingly globalized world, meeting the needs and requirements for users from different cultural backgrounds is crucial for the safety and health of users, as well as survival of the company. In this research a cross cultural product design survey was tested for its suitability and reliability. Method/Statistical Analysis: A short review of the past cross cultural models such as Hofstede (1980), Hall (1973), Trompenaars (1997) and Lee (2001) was conducted, as well as the pilot testing of Lee’s quantitative cross cultural product design survey instrument and a pilot study involving 36 Malaysian undergraduate students were conducted. Reliability and suitability of survey instrument were tested with Cronbach’s Alpha and Kolmogrov Smirnov analysis. Results: Cronbach’s Alpha value for the overall survey instrument reliability was 0.387. Referring to the values for each scale in the survey instrument the highest Cronbach Alpha value was 0.499, and the lowest was -0.135. Kolmogorov Smirnov test showed that for almost all of the survey items responses had a non-normal data distribution. Conclusion/Application: A cross cultural product design survey needs to be reliable and valid. In this study, the proposed survey instrument showed poor reliability. Quantitative assessment method has yet to prove itself their suitability in cross cultural product design research.